The Effect Of Individual Competence, Compensation And Organizational Climate On Employee Performance With Job Satisfaction As An Intervening Variable - Atif Rehman; Mar’atus Solikhah (Publikasi Indonesia, 2024)
This research entitle of “Analysis influence of Individual Competence, Compensation and Organization Climate to Employee Performance with Job Satisfaction as Intervening Variable” (Case Study at Kospin Ibnu Khaldun Cirebon)”. This research target is : To gain an understanding of the influence of the individual competence, compensation and organization climate to employee performance with job satisfaction as intervening variable. At this research used by purpossive sampling as much 45 responders. As for examination of at this research done with validity test, reliability, classical assumptions, hypothesis test in the form of t test, F test, coefficient determinant, path analysis and sobel test. With multiple linear regression analysis at this research obtained by result b1 = 0,187 showing influence which are positive of Individual Competence variable to Employee Performance, b2 = 0,258 showing influence which are positive of Compensation to Employee Performance, b3 = 0,289 showing influence which are positive of Organization Climate variable to Employee Performance, b4 = 0,261 showing influence which are positive of Job Satisfaction variable to Employee Performance. Whereas for partial hypothesis testing the t test was used, obtained the tcount for Individual Competence to Employee Performance of 2,446, tcount for Compensation variable to Employee Performance of 3,090, tcount for Organization Climate to Employee Performance of 2,528 and tcount for Job Satisfaction variable to Employee Performance of 2,281. Then based on the results of calculations through the sobel test, Job Satisfaction mediate the relationship between Individual Competence, Compensation and Organization Climate to Employee Performance.